Analysis of Facial Expressions for Predicting Student’s Learning Level - S, Vidyadhari; Mishra, Dhirendra S (International Journal of Computer Sciences and Engineering, 2020)
In today’s scenario, there is an explosion of knowledge and the context of what is learnt and how it is learnt by the students become very important to understand. Student needs to develop their higher order thinking skills which would help them understand and apply concepts in the right manner. This research work specifically focuses on emotion detection of the students by analysing their facial expressions while they are answering a set of questions asked by an instructor for different subjects. The aim is to identify the cognitive learning level of the Bloom’s Taxonomy and map the emotions set to each learning level. This is achieved by capturing the emotions of students from an emotion classifier based on CNN (Convolutional Neural Networks) and further classifying them using various classification algorithms which in turn predicts the Accuracy of the proposed system.